Syllabification of Standard Lithuanian in terms of the sonority theory - Kazlauskienė, Asta (Vilnius University Open Series, 2022)
The article discusses the research which aims to ascertain whether the sonority of sounds could be used to determine boundaries of syllables in consonant clusters and if this principle is commonly employed by a sample of language users. The research consists of a) the overview of more significant foreign authors’ works, which is then used to identify the theoretic hierarchy of consonant clusters in Lithuanian, b) the exploratory analysis of consonant sonority, c) the investigation of sonority in consonant clusters, d) the research of tendencies in language users’ syllabification. The results have revealed that after establishing the hierarchy of consonant clusters in Lithuanian and applying the principle of syllabification by sonority, one fifth of the consonant clusters in the empirical data base is impossible to syllabify. Neither predicted phonetic syllable, nor the phonological syllable is commonly employed by the language users. The users are likely to assign at least one consonant of a cluster to a preceding syllable, while only the last consonant of polynomial clusters is assigned to the onset of a later syllable. Fricative consonants in consonant clusters are assigned to the coda of a previous syllable.